Transformasi Kedudukan Bapedal Sebagai Kelembagaan Pengelolaan Lingkungan Hidup Pada Pemerintah Pusat dan Pemerintah Daerah - Prasetiyo, Dimas Agung; Awiati, Wiwik (UNES Law Review, 2023)
Lawrence M. Friedman divides the legal system into three subsystems, namely legal substance, legal structure, and legal culture. Environmental management must include these three aspects. Environmental institutions such as Bapedal have an important role in overseeing and regulating environmental policies. There are obstacles in synchronizing regulations between central and local governments and overlapping authority between sectors. Institutional reconstruction and transformation are needed to improve the effectiveness and efficiency of environmental management. The issues in this paper involve the institutional transformation of Bapedal and the regulation of the agency's authority in local government. Normative legal research methods are used to conclude the importance of coordination between central and local governments in environmental management and the need for uniformity of institutional nomenclature throughout Indonesia. Local governments should support environmental impact control institutions by providing appropriate main tasks and functions. Efficient coordination and supervision are needed, and institutional nomenclature should be uniform. Human resources also need to be well organized, and the Ministry of Environment and Forestry can play a role in institutional development in the regions.